Interview. Issue 3 (5th June 2018) - Haszeldine, Stuart
Abstract: Perhaps the most significant issue for some countries where curbing carbon emissions is concerned is not the capture or the transport, but the storage. The reality is the ideal geology is needed for the safe storage of carbon dioxide and for some countries this is not necessarily a straight forward issue. However a novel approach has been developed through a UK/China research team which could open up whole new reservoirs of storage in those geographical regions where, currently, storage options are limited. In this article Professor Stuart Haszeldine (PSH), from the University of Edinburgh's School of GeoSciences, explains the most recent developments in CO2 storage to GHGS&T.